P-C8 Directly acting antiviral therapies have differential effects on cellular and soluble markers of inflammation in success-fully-treated HIV/HCV co-infected patients. (March 2017) - Wilson, Eleanor; Lee, Rebecca; Ward, Haley; Howard, Louisa; Rosenthal, Elana; Shrivastava, Shikha; Kohli, Anita; Kottilil, Shyam; Masur, Henry
Abstract : Background: HIV/HCV co-infected patients have higher levels of immune activation and accelerated fibrogenesis. We compared markers of immune activation in HIV/HCV co-infected subjects successfully treated for HCV with one of three DAA-only regimens in order to determine if different agents have different effects. Methods: Two prospective phase II studies conducted at the NIH Clinical Center studied DAA-only regimens [SOF/LDV for 12 weeks in ERADICATE (NCT01878799) and DCV/ASV, two drugs for 24 weeks, or with beclabuvir for 12 weeks in CONQUER (NCT02124044)] in HIV/HCV genotype 1 co-infected subjects. We tested paired pre/post-treatment samples from a subset of patients via a multiplex assay (ProcartaPlex Human Cytokine & Chemokine Panel, eBioscience) and flow cytometry for markers of activation (CD38, HLA-DR) and exhaustion (TIM-3, PD-1, CTLA-4). Median values are reported; comparisons were made using Wilcoxon Rank tests. To correct for multiple comparisons, P<0.02 was considered significant. Results: Subjects from ERADICATE (2E, n = 6), CONQUER 2DAA arm (2C, n = 7) and CONQUER 3DAA arm (3C, n = 7) were comparable in terms of sex, age, race, fibrosis, and CD4 counts. 2E subjects were HCV treatment naïve; 20% of 2C subjects and 58% of 3C subjects were treatment-experienced. All CONQUER patients were on ART, compared to 67% of included 2E subjects. All groups had a significant decline in the percentage of circulating activated T cells, while 3C patients showed a significant decline in chemokines and pro-inflammatory cytokines, particularly IL-10, IL-1R, IL-8, IP10, and MIP-1 beta. Conclusions: In this study, SVR is associated with reduced cellular activation, resulting in reduced cytokine production. The addition of NS3 inhibitor appears to improve resolution of cellular and soluble markers of immune activation.